Fish oil consumption prevents glucose intolerance and hypercorticosteronemy in footshock-stressed rats - Spadari-Bratfisch Regina C; Oller do Nascimento Claudia M; Ribeiro Eliane B; Pisani Luciana P; Souza Gabriel IH; Cunha Claudio A; Scarmagnani Flavia R; Eguchi Ricardo; Oyama Lila M (Lipids in Health and Disease, 2011)
Abstract Background Environmental stress plays an important role in the development of glucose intolerance influencing lipid and glucose metabolism through sympathetic nervous system, cytokines and hormones such as glucocorticoids, catecholamines and glucagon. Otherwise, fish oil prevents glucose intolerance and insulin resistance. Although the mechanisms involved are not fully understood, it is known that sympathetic and HPA responses are blunted and catecholamines and glucocorticoids concentrations can be modulated by fish consumption. The aim of the present study was to evaluate whether fish oil, on a normal lipidic diet: 1) could prevent the effect of footshock-stress on the development of glucose intolerance; 2) modified adiponectin receptor and serum concentration; and 3) also modified TNF-α, IL-6 and interleukin-10 (IL-10) levels in adipose tissue and liver. The study was performed in thirty day-old male Wistar randomly assigned into four groups: no stressed (C) and stressed (CS) rats fed with control diet, and no stressed (F) and stressed (FS) rats fed with a fish oil rich diet. The stress was performed as a three daily footshock stress sessions. Results Body weight, carcass fat and protein content were not different among groups. FS presented a reduction on the relative weight of RET. Basal serum glucose levels were higher in CS and FS but 15 min after glucose load just CS remained with higher levels than other groups. Serum corticosterone concentration was increased in CS, this effect was inhibited in FS. However, 15 min after footshock-stress, corticosterone levels were similar among groups. IL-6 was increased in EPI of CS but fish oil consumption prevented IL-6 increase in FS. Similar levels of TNF-α and IL-10 in RET, EPI, and liver were observed among groups. Adipo R1 protein concentration was not different among groups. Footshock-stress did not modify AdipoR2 concentration, but fish oil diet increases AdipoR2 protein concentration. Conclusions Footshock-stress promotes glucose intolerance associated to corticosterone serum level and epididymal white adipose tissue IL-6 concentration increase. The fish oil consumption by stressed rats normalized the stress responses. These results suggested that fish oil intake could be useful to minimize or prevent the development of diseases associated to the stress.